Inclusive Experiences in Pre-Professional Practices of the Online Early Childhood Education Program at Milagro State University Using Plithogenic Statistics - Marylin Figueroa Cruz; María Elena Ron Vargas (Neutrosophic Sets and Systems)
Early Childhood Education sets a series of pedagogical, didactic and psychological skills with the focus of supporting education in the various areas of human development of children in early childhood. It assesses training for Higher Education professionals who can perform in this educational context. This work connects one experience of preprofessional practice in the early childhood education program, held through virtual modality, since the seventh promotion, connected to one subject, in a preventive, trans disciplinary, intersectoral and communitarian approach. This established experience has allowed empowering in student’s inclusive teacher competencies that give them the opportunity to provide a good educational service to minors, especially those with neurodevelopmental disabilities, having parents and teachers as mediators of the educational process. The investigation is composed of a mixed methods approach with a plithogenic statistical analysis that partitions uncertainty regarding inclusive competencies and diverse educational service, the need for which is complemented by a validating qualitative analysis.